2017
DOI: 10.1111/jce.13171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cardiac Resynchronization Therapy on Myocardial Fibrosis and Relevant Cytokines in a Canine Model With Experimental Heart Failure

Abstract: By means of coordinating LV dyssynchrony, cellular and molecular reverse remodeling relevant to fibrosis inhibition could also be invoked by CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Such changes were accompanied by left ventricular reverse remodelling, a reversal of the HF‐induced left ventricular dilatation . Newer studies now also provide molecular mechanism of these favourable changes, indicating restoration of left ventricular cardiomyocyte diameter, suppression of collagen deposition, and most importantly, down‐regulation of transforming growth factor (TGF)‐β 1 cytokines linked to lower levels of the matrix glycoprotein, osteopontin, required for the activation of fibroblasts upon TGF‐β 1 stimulation . As we know from large clinical trials, however, LVEF is linked to HF risk as a continuum up to an LVEF of 45%; therefore it is conceivable that the aforementioned benefits would be present in those with a higher ejection fraction, as indicated in our current analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Such changes were accompanied by left ventricular reverse remodelling, a reversal of the HF‐induced left ventricular dilatation . Newer studies now also provide molecular mechanism of these favourable changes, indicating restoration of left ventricular cardiomyocyte diameter, suppression of collagen deposition, and most importantly, down‐regulation of transforming growth factor (TGF)‐β 1 cytokines linked to lower levels of the matrix glycoprotein, osteopontin, required for the activation of fibroblasts upon TGF‐β 1 stimulation . As we know from large clinical trials, however, LVEF is linked to HF risk as a continuum up to an LVEF of 45%; therefore it is conceivable that the aforementioned benefits would be present in those with a higher ejection fraction, as indicated in our current analysis.…”
Section: Discussionmentioning
confidence: 99%
“…TGF- β 1 plays multiple regulatory roles in fibrosis remodeling through smad's dependent pathway in many diseases [ 21 ]. During HF or myocardial ischemia, TGF- β 1 signaling can induce fibrosis of cardiac fibroblasts and promote the synthesis of collagen and fibronectin, finally promoting myocardial fibrosis [ 22 ]. In the present study, H 9 C 2 cells were transfected with miRNA-132 mimics and miRNA-132 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…mechano-electric feedback). [ 18 ] Besides restoring cardiomyocyte size, there is improvement in kinetics of intracellular calcium cycling through up regulation of SERCA, RyR, and sodium-calcium exchanger levels in patients responding to CRT while no significant change is observed in nonresponders [ 1 , 2 ]. Furthermore, Aiba et al demonstrated in an animal model of LV dyssynchrony, a reduction in inward rectifier potassium current and delayed rectifier potassium current, which was associated with APD prolongation [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical coordination of left ventricle (LV) with long-term cardiac resynchronization therapy (CRT) has been shown to reverse LV structural and molecular remodeling in cardiomyopathy patients with wide left bundle branch block (LBBB) and LV dysfunction. In particular, sarcomeric proteins, sarcoplasmic reticulum calcium ATPase 2α (SERCA) and ryanodine receptor (RyR) levels are restored, resulting in augmentation of excitation-contraction coupling and intracellular calcium cycling [ 1 , 2 ]. In addition, restoration of electric LV conduction direction may reverse chronic LBBB-related action potential duration (APD) heterogeneity arising from long-term cardiac memory [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%